True, justified, belief? Partisanship weakens the positive effect of news media literacy on fake news detection - Sude, Daniel Jeffrey; Sharon, Gil; Dvir-Gvirsman, Shira (Frontiers in Psychology, 2023)
To investigate how people assess whether politically consistent news is real or fake, two studies (N = 1008; N = 1397) with adult American participants conducted in 2020 and 2022 utilized a within-subjects experimental design to investigate perceptions of news accuracy. When a mock Facebook post with either fake (Study 1) or real (Study 2) news content was attributed to an alternative (vs. a mainstream) news outlet, it was, on average, perceived to be less accurate. Those with beliefs reflecting News Media Literacy demonstrated greater sensitivity to the outlet’s status. This relationship was itself contingent on the strength of the participant’s partisan identity. Strong partisans high in News Media Literacy defended the accuracy of politically consistent content, even while recognizing that an outlet was unfamiliar. These results highlight the fundamental importance of looking at the interaction between user-traits and features of social media news posts when examining learning from political news on social media.